Orphaned children's view on the outreach programs a goal free evaluation - Mendoza, Claudia Marie B.; Bantang, Joanne R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This qualitative research identified the learning outcomes and how orphans apply what they have learned from outreach programs, including their attitudes towards those outreach programs. Twenty orphans from Manila Boys Town Complex were selected through criterion sampling. Data were gathered through in depth interviews, which were transcribed and content analyzed using the framework of Scrivens Goal Free Evaluation 1991. The learning outcomes of program recipients can be categorized into knowledge, skills, and attitudes. Results show that the girls retain more information about the things they learned from the outreach programs compared to the boys. In fact, only the girls remembered lessons in the knowledge domain such as menstruation, reproductive system, English grammar and vocabulary, proper hygiene, and trash segregation. All orphans learned skills about exercising through physical activities, planting, and particularly for girls, craftmaking. Finally the orphans learned values such as being hopeful, happy, sociable, diligent, persistent, confident, and helpful to others. They all shared that they are able to apply what they have learned in their daily life and in school. What the orphans appreciated the most from the outreach programs are the opportunity to interact, to participate in alternate activity, and to receive gifts from program proponents. Their disinterest for it, however, boils down to the strategy or approach in conducting the outreach program. As the results of the Goal Free Evaluation conducted, there seems to be a match between what the orphans learned and the programs intentions as designed by the program proponents. However, the things that they have learned do not necessarily match what they need. Some lessons did not have long term retention on the orphans. This research suggests a need to implement a formal needs assessment of the program recipients so that the delivered programs can readily answer their needs. It is recommended that the outreach programs be made orphaned-centered and use sport related programs, challenging games, and educational field trips. For future researches, an examination of best practices in program implementation on wider assessment of outreach programs could be implemented for greater impact.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Orphans -- Philippines -- Social services for